2017
DOI: 10.1074/jbc.m117.785287
|View full text |Cite
|
Sign up to set email alerts
|

Structure and energetics of pairwise interactions between proteasome subunits RPN2, RPN13, and ubiquitin clarify a substrate recruitment mechanism

Abstract: The 26S proteasome is a large cellular assembly that mediates the selective degradation of proteins in the nucleus and cytosol and is an established target for anticancer therapeutics. Protein substrates are typically targeted to the proteasome through modification with a polyubiquitin chain, which can be recognized by several proteasome-associated ubiquitin receptors. One of these receptors, RPN13/ADRM1, is recruited to the proteasome through direct interaction with the large scaffolding protein RPN2 within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 68 publications
(89 reference statements)
4
59
0
Order By: Relevance
“…We found that, titrating unlabeled K48-diUb to 15 N-labeled Rpn13 causes large chemical shift perturbations (CSPs), which mainly involve residues 73-83 and 93-106 ( Fig 3a). These residues form a contiguous surface on Rpn13, covering an area larger than expected from the previously determined complex structure between Rpn13 NTD and Ub monomer 6,7 . On the other hand, titrating unlabeled Rpn13 NTD to K48-dUb, with either proximal or distal Ub 15 N-labeled and the other subunit unlabeled, the CSPs are mainly observed for residues in the β-sheet region of both Ub subunits.…”
Section: Solution Structure Of Rpn13 Ntd :K48-diub Complexmentioning
confidence: 82%
See 2 more Smart Citations
“…We found that, titrating unlabeled K48-diUb to 15 N-labeled Rpn13 causes large chemical shift perturbations (CSPs), which mainly involve residues 73-83 and 93-106 ( Fig 3a). These residues form a contiguous surface on Rpn13, covering an area larger than expected from the previously determined complex structure between Rpn13 NTD and Ub monomer 6,7 . On the other hand, titrating unlabeled Rpn13 NTD to K48-dUb, with either proximal or distal Ub 15 N-labeled and the other subunit unlabeled, the CSPs are mainly observed for residues in the β-sheet region of both Ub subunits.…”
Section: Solution Structure Of Rpn13 Ntd :K48-diub Complexmentioning
confidence: 82%
“…This would explain a 2:1 stoichiometry between K48-diUb and Rpn13 NTD , or a 1:1 stoichiometry between Ub monomer and Rnpn13 NTD previously observed in bulk titrations 3,7,9 . Indeed, the Rpn13 NTD -Ub complex has been crystalized as a dimer ( Supplementary Fig. S14) 7 . Herein, the structure of Rpn13 NTD :K48-diUb complex clearly explains how the two Ub subunits of K48-diUb simultaneously interact with Rpn13 NTD .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In another observation, different binding interactions between proteasome subunits, viz. RPN13, RPN2, and ubiquitin, were substantiated for substrate recruitment in proteasome, using surface plasmon resonance and fluorescence polarization . The gating mechanism and the energetics of 20S proteasome core particle in T. acidophilum were shown by solution NMR technique …”
Section: Recent Findings Decipher Cellular Physiological Functions Ofmentioning
confidence: 99%
“…RPN13, RPN2, and ubiquitin, were substantiated for substrate recruitment in proteasome, using surface plasmon resonance and fluorescence polarization. 102 The gating mechanism and the energetics of 20S proteasome core particle in T. acidophilum were shown by solution NMR technique. 103 Ubiquitous involvement of proteasome in different cellular pathways and the wider linkages due to lack of functions associated with many diseases has prompted scientists to propose this multiproteinase complex as a suitable target for remedial interventions.…”
Section: Of Proteasomementioning
confidence: 99%